Computational Prediction of Potent Therapeutic Targets of Pseudomonas Syringae and in Silico Virtual Screening For Novel Inhibitors - PRADEEP K. NAIK; SENEHA SANTOSHI; ASHIMA BIRMANI (International Journal of Pharma and Bio Sciences, 2010)
Pseudomonas syringae is a plant pathogen which infects a wide range of plant species, and is also the causative organism of bacterial brown spot of bean. The complete genome sequence of pathogen has provided all the determinants of host-pathogen interactions and possible drug targets, computational methods for selecting suitable candidates for further experimental analyses are currently limited. We have performed comparative analysis of genomes and metabolic pathways of the pathogen P. syringae and the host phaseolus vulgaris (kidney bean) and identified eight potent therapeutic targets. After critical evaluations of the targets we have considered murD and murE as the potent targets for virtual screening of lead molecules. Virtual screening was carried out using the high throughput virtual screening protocol and PubChem drug database. The interaction studies provided promising ligands for future experimental screening to inhibit the proliferation of Pseudomonas syringae.